Zamek jako metafora. Podróże po literaturze = The castle as a metaphor. A journey through literature - Malinowski, Wiesław Mateusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article addresses the notion of three categories of metaphors generated by the image of a castle in the selected works of the 19th-century literature of France, Belgium and Poland. The paper discusses the castle of soul (Nerval, Maeterlinck, Miciński), the castle of tyranny (Hugo, Custine) and the castle of glory (Mickiewicz, Goszczyński).
Keywords: Zamek; metafora; literatura; 19 w.; castle; metaphor; literature; 19th century